Influence of HIV Infection and Antiretroviral Therapy on Bone Homeostasis - Delpino, María Victoria (2020)
The human immunodeficiency virus type 1 (HIV)/AIDS pandemic represents the most significant global health challenge in modern history. This infection leads toward an inflammatory state associated with chronic immune dysregulation activation that tilts the immune-skeletal interface and its deep integration between cell types and cytokines with a strong influence on skeletal renewal and exacerbated bone loss...